GREEN PURCHASING: AN EFFECTIVE INTEGRATED PROCESS OF SUPPLY CHAIN PERSPECTIVE IN MTT PRIORITY (Journal of Technology and Operations Management, 2018)
Green purchasing has become a significant priority for organizations and related parties to ensure a sustainable environment and future. Organizations should practise green purchasing because it provides a lot of benefits to the internal part of organization and to the external environment. The objective of this research is to examine the significant effectiveness of green fundamentals of purchasing and supply management, purchasing administration and materials management in enhancing the integrated purchasing and supply management process (green purchasing). This research focuses on a company that practising best in green purchasing that is Malaysia Trade and Transport Priority (MTT Priority). 20 Questionnaires were distributed to the employees and interviews were conducted with the Chief Executive Officer (CEO) and General Manager (GM) in the company. Green fundamentals of purchasing and supply management, purchasing administration and materials management are the independent variables for the green purchasing. Theoretically, it contributes an insight study on how the independent variables will affect green purchasing and benefit the company. Practically, this research is applicable for organizations in various industries, especially those who are operating business, in making important decisions to improve sustainable operations. Based on this research, it is found that there is positive outcome to promote Green Purchasing in the business organizations.